Insights from the largest diverse ancestry sex-specific disease map for genetically predicted height - A. Papadopoulou; E. M. Litkowski; M. Graff; Z. Wang; R. A. J. Smit; G. Chittoor; I. Dinsmore; N. S. Josyula; M. Lin; J. Shortt; W. Zhu; S. L. Vedantam; et al. (npj Genomic Medicine)
Abstract We performed ancestry and sex specific Phenome Wide Association Studies (PheWAS) to explore disease related outcomes associated with genetically predicted height. This is the largest PheWAS on genetically predicted height involving up to 840,000 individuals of diverse ancestry. We explored European, African, East Asian ancestries and Hispanic population groups. Increased genetically predicted height is associated with hyperpotassemia and autism in the male cross-ancestry analysis. We report male-only European ancestry associations with anxiety disorders, post-traumatic stress and substance addiction and disorders. We identify a signal with benign neoplasm of other parts of digestive system in females. We report associations with a series of disorders, several with no prior evidence of association with height, involving mental disorders and the endocrine system. Our study suggests that increased genetically predicted height is associated with higher prevalence of many clinically relevant traits which has important implications for epidemiological and clinical disease surveillance and risk stratification.